Maghltay resources and method in his book ` al tarajim al sakita men ketab tahtheb al kamal (Journal of the College of Basic Education, 2023)
The study of Arab Muslim historians is one of the most important historical studies , as it reveals an important link in the episodes of the nation intellectual heritage , as it defines features of arab Islamic history and then this study consolidates the approach of historical research .The importance of this study comes Maghltay considered one of the most prominent arab muslim scholars and thinker in the eighth century AH , and who in varios scientific fields , including his book ` al tarajim al sakita men ketab tahtheb al kamal ` the subject of our study .